A strong-coupled method combined finite element method and lattice Boltzmann method via an implicit immersed boundary scheme for fluid structure interaction. (15th October 2020) - Li, Weizhong; Wang, Wen-Quan; Yan, Yan; Yu, Zhi-Feng
Abstract: Fluid structure interaction (FSI) problems are often encountered in ocean science and technology. In this present, an implicit immersed boundary (IB) method combined with Lattice Boltzmann Method (LBM) and finite element method (FEM) is presented for the strong-coupled simulations of fluid structure interaction. Velocity field is solved rapidly by lattice Boltzmann-BGK equations without external force, and the deformation of a flexible structure was computed by FEM. Fluid structure coupling was processed by immersed boundary implicit forced method. The resulting combination gives an easy-to-use, inexpensive and accurate technique to solve FSI problems. Simultaneously, the body force on the immersed boundary can be calculated directly and acts as the load for structure solver, so the displacement of structure can be obtained at the same time, which is avoid the time lag between the fluid solver and solid solver. Several examples including flow over a static and deformable plate, and the flow problems of an oscillating and cantilever flexible plate were simulated and analyzed. The results agree well with the previous experimental and numerical investigations, which indicate the IB-LB-FEM proposed in this paper is an efficient and reliable fluid-structure interaction numerical simulation method. Highlights: Extend the implicit velocity correction method to simulate complex fluid structure interaction. Implicit immersed boundary method to combined LBM and FEM is presented. Strongly-coupled fluid structure interaction is presented for stable solution.